Doing Giftedness: Reification and Performance in Israeli Parentsâ Discourse of their Gifted Children - Eliaz, Yoad (Social Science Learning Education Journal, 2017)
This article explores the discursive practices employed by parents of gifted children to identify, construct and mobilize âchild giftedness.â Using qualitative analysis of interviews with Israeli parents of gifted children and an internet forum for parents of gifted children in Israel, I draw on critical constructionism to explore the relationships between gifted and non-gifted, ârealâ and âfakeâ gifted children, as well as between âidealâ and âpushyâ parents. The findings show how, in shaping the social identity of their gifted child as well as of themselves, parents employ two major practices, related to the reification and performance of giftedness. These two practices are examined as representing opposite yet complementary aspects of the ways in which parents are âdoing giftednessâKeywords: Giftedness, gifted childrens parents, pushy parents